Teoria das provas e fato jurídico no processo administrativo tributário - Kirchner, Juliana Leite (2012)
The purpose of this study, presented here, is to investigate the relevance of the evidence for the formation of tax legal fact, under the scope of the tax levy. We will undertake the review about the important role that events play in relations between the state and taxpayers, through the deeds of release, for the characterization of tax legal fact and, consequently, the formation of the tax credit. The focus of the approach we want to achieve is to demonstrate that the evidence makes it extremely important in the context of tax impact, so we aim to highlight their support for the indispensability of individual standards and concrete by the Public Administration and therefore the act tax administrative release from elements collected in fiscalizatórios procedures. Still, we aim to demonstrate the importance of evidence in tax percussion, demonstrating the importance of the legal facts tributaries consisting only if grounded in law admitted in evidence in the administrative headquarters of tax, in order to preserve the rights and fundamental guarantees of taxpayers. We intend therefore to conduct a study on the tax legal fact and evidence, and in particular, the administrative tax process, through the demonstration of relevant legislation and case law and administrative practice examples